Arsitektur Strategi Pengembangan Bisnis Pelabuhan Darat - Michael Jourdan; Lukman M. Baga; Harianto Harianto (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2018)
The purpose of this study is to identify internal and external factors that influence CDP business development, formulate business development strategies, and design CDP strategic architecture. Cikarang Dry Port (CDP) is a land port designed to support export and import activities and supply chains in the Jabodetabek and Cikarang regions. The precise business development strategy to optimize resources and opportunities for the CDP business environment is important to develop. The method of this research is descriptive analysis and purposive sampling. The analytical tools used include internal and external analysis and SWOT. The results show that the IFE and EFE values obtained are 3.03 and 3.07. Its main strength is the availability of land port’s capacity with a score of 0.56. The external factors that provide significance relative to the success of dry port development are internet usage and applications on smartphones that scored 0.32. The regulation on expansion and business development of the Kalibaru Port (Newport Priok Container Terminal) is the biggest threat of 0.06 and 0.04.